1993
DOI: 10.1212/wnl.43.3_part_1.609
|View full text |Cite
|
Sign up to set email alerts
|

Dural enhancement and cerebral displacement secondary to intracranial hypotension

Abstract: We studied a patient with spontaneous intracranial hypotension whose gadolinium-enhanced MRI revealed an extraordinary degree of dural enhancement and striking displacement of the optic chiasm, flattening of the pons, and downward displacement of the cerebellar tonsils. These changes were reversed when a CSF leak at the site of a T12-L1 arachnoid cyst was closed following an epidural blood patch. Such diffuse meningeal enhancement results from the dural venous dilatation that accompanies a reduced CSF volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
203
3
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(215 citation statements)
references
References 0 publications
5
203
3
4
Order By: Relevance
“…Despite the improvements in diagnostic modalities, the early diagnosis still depends on the clinician's foresight. Although it is reported that the majority of the IH cases show diffuse meningeal enhancement on cranial MRI [2], there are cases reported in which no enhancement is encountered and enhancement should not be regarded as an absolute finding of IH [6,8]. In the present case, cranial MRI also revealed nothing abnormal, but the clinical picture and the past medical history forced us to think that this might be a secondary IH case.…”
Section: Discussionmentioning
confidence: 46%
“…Despite the improvements in diagnostic modalities, the early diagnosis still depends on the clinician's foresight. Although it is reported that the majority of the IH cases show diffuse meningeal enhancement on cranial MRI [2], there are cases reported in which no enhancement is encountered and enhancement should not be regarded as an absolute finding of IH [6,8]. In the present case, cranial MRI also revealed nothing abnormal, but the clinical picture and the past medical history forced us to think that this might be a secondary IH case.…”
Section: Discussionmentioning
confidence: 46%
“…In SIH, loss of CSF volume from a CSF leak, results in a compensatory increase in blood volume, namely intracranial venous hyperemia, in order to maintain a constant intracranial pressure (ICP). Once venous compensation is maximized, subdural fluid collections may accumulate to provide further volume for maintaining ICP 4,25,26 . The CSF pressure decreases when the rate of CSF volume loss cannot be further compensated by these mechanisms 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) reveals diffuse meningeal thickening, gadolinium enhancement, and subdural fluid collections (hygromas and rarely haematomas), at times associated with diminished size of the subarachnoidal cisterns, with the descent of the cerebellar tonsils or with flattening of the optic chiasm [4][5][6][7][8][9]. In such cases, differential diagnosis with systemic diseases like rheumatoid arthritis, mucopolysaccaridosis, sarcoidosis and meningeal carcinomatosis must be performed [10][11][12].…”
Section: B R I E F R E P O R T C Lia (౧)mentioning
confidence: 99%
“…The latter two tests may reveal single or multiple meningeal diverticula at cervical or thoracic spinal level, which may lead to dural tearing [4][5][6][7][8]. Still, the correct localisation of dural tearing may not be shown because of the limits of the current imaging techniques.…”
Section: B R I E F R E P O R T C Lia (౧)mentioning
confidence: 99%